PENGARUH MOTIVASI, KEPEMIMPINAN, DAN BUDAYA ORGANISASI TERHADAP KEPUASAN DAN KINERJA KARYAWAN PADA PT. XYZ - Avissa Muharamah Salsabila Divitri; Daniel Ong Kim Kui (Journal of Innovation Research and Knowledge, 2026)
The insurance industry plays a critical role in sustaining economic stability through effective risk management. PT. XYZ, a state-owned general insurance company, faces ongoing challenges in enhancing employee performance. This study examines the effects of work motivation, leadership, and organizational culture on job satisfaction and employee performance, with job satisfaction serving as a mediating variable. A quantitative approach was employed, involving a survey of 125 active employees selected via Proportionate Stratified Random Sampling. Data were collected using a 5-point Likert scale questionnaire and analyzed with Structural Equation Modeling (SEM) using Partial Least Squares (PLS). Findings indicate that work motivation, leadership, and organizational culture exert positive and significant influences on job satisfaction. Job satisfaction fully mediates the relationships between these independent variables and employee performance. Work motivation emerges as the dominant driver of both satisfaction and performance, whereas the impact of organizational culture varies by internal context. These results provide strategic implications for management in human resource development, emphasizing motivation, transformational leadership, and a supportive organizational culture